Sectoral Classification and Inequality of Kedungsepur National Strategic Area of Central Java Province - Pratama, Arik Wahyu; Taufiqqurrachman, Fahrizal (Trunojoyo University of Madura, 2025)
This study examines economic inequality in the Kedungsepur National Strategic Area, Central Java Province, which is still high despite the potential of leading sectors in each region. The objective is to identify leading sectors and analyze economic inequality in the region. The methods used include Location Quotient (LQ), Dynamic Location Quotient (DLQ), and Klassen Typology analysis, with secondary data from the Central Bureau of Statistics during the 2019-2023 period. The results show four leading sectors: Agriculture, Forestry, and Fisheries in Kendal; Government Administration in Demak; and Financial Services in Grobogan. However, not all regions have leading sectors, such as Semarang and Salatiga. The Williamson Index reveals that economic inequality in the region is still significant, indicating the need for strategies to maximize the potential of the leading sectors.In conclusion, although there are leading sectors that can boost the economy, inequality between regions in KSN Kedungsepur remains a challenge that must be overcome to achieve more equitable development.